Meningkatkan Prestasi Dan Kualitas Belajar Pelajaran Bahasa Indonesia Pada Materi Berbicara Dan Membaca Dengan Menerapkan Metode Stad Dan Metode Role Playing Pada Siswa Kelas VI SDN 12 Pelerang - Samson Bahari (STIKes Ibnu Sina Ajibarang, 2023)
The success of learning objectives is determined by many factors, including the teacher factor in carrying out the teaching and learning process, because teachers can directly influence, develop and improve students' intelligence and skills. To overcome the problems above and to achieve educational goals optimally, the role of teachers is very important and it is hoped that teachers have good teaching methods/models and are able to choose appropriate learning models that are in accordance with the concepts of the subjects to be conveyed. Problems to be studied in this research are: (a) How does student learning achievement increase with the implementation of STAD and Role Playing learning models? (b) What is the influence of the STAD and Role Playing learning methods on student learning motivation? The purpose of this action research is: (a) Want to know the increase in student learning achievement after implementing the STAD and Role Playing learning models. (b) Want to know the effect of student learning motivation after implementing the STAD and Role Playing learning methods. This research uses three rounds of action research. Each round consists of four stages, namely: design, activities and observations, reflection, and revision. The target of this research is Class VI students of SDN 12 Pelerang for the 2021/2022 academic year. The data obtained are in the form of formative test results, observation sheets of teaching and learning activities. From the results of the analysis it was found that student learning achievement had increased from cycle I to cycle III, namely, cycle I ( 68.18%), cycle II (77.27%), cycle III (86.36%). The conclusion of this research is that the STAD and Role Playing model methods can have a positive influence on the learning motivation of Class VI Students at SDN 12 Pelerang for the 2021 Academic Year /2022 and this learning method can be used as an alternative for learning Indonesian.